Residents’ perceptions on road hump effectiveness in Malaysian residential environments - Bachok, Khairun Sarah Radhiah; Kadar Hamsa, Abdul Azeez; Mohamed, Mohd Zin; Ibrahim, Mansor (Avestia Publishing, 2018)
Two common concerns for residents in their respective residential areas are high traffic speeds and noise levels. This paper analyses the perception of residents on the effectiveness of road humps in improving residential living environment based on their effects on traffic speed and noise. The study was conducted in three Malaysian residential areas, specifically Putrajaya, Taman Setiawangsa, and Keramat. A questionnaire survey was distributed to 478 respondents asking for their perceptions on whether road humps have improved their living environment by reducing speed and noise. Binary logistic regression models were also developed to identify variables that affect respondents’ likelihood to agree that existing road humps have improved the living environment of the residents by reducing traffic speed and noise. The result of this study is that the height of road humps affects noise levels and traffic speeds, as average vehicle speeds and LAeq were lowest at the road hump of 90mm height. The respondents’ perceptions of the importance of lower traffic speeds and noise levels, as well as the appropriateness of hump heights and locations, were significant variables in determining the likelihood of their agreement that road humps have improved their living environment.